Vector Bond Graph Method for the Dynamics Analysis of Planar Linkage based on Generalized Velocity - Wang Zhongshuang; Xu He (Jixie chuandong)
For improving the reliability and efficiency of the dynamics analysis for planar linkage,the corresponding vector bond graph procedure based on generalized velocity is proposed. By the kinematic analysis of mechanism,the relation matrix between mechanism velocity vector,the capacitance field velocity vector,the inertia field velocity vector,the resistive field velocity vector,the source field velocity vector and generalized velocity vector are established. Based on these,the vector bond graph model of planar linkage based on generalized velocity is established. By the corresponding algorithm,the automatic dynamics modeling,calculation and analysis of planar six bar press mechanism on a computer is realized,the influence of pulse working load on mechanism driving moment is revealed,and the validity of the procedure proposed is verified.